Ritratti moderni di Cicerone nelle epistole agli antichi di Petrarca (fam. xxiv 3 e 4) - Modern Portraits of Cicero in Petrarch’s Letters to the Ancients (fam. Xxiv 3 and 4) - Boldrer, Francesca (Ciceroniana On Line, 2019)
The paper conducts a reading of Petrarch’s letters 24, 3 and 4 in which the author addresses Cicero as an ideal correspondent and which contain two contrasting portraits of the Latin orator in the wake of the discovery of a great part of Cicero’s epistolary corpus. I study the development of Petrarch’s moral and literary views on Cicero with a focus on the decidedly modern spirit with which Petrarch rediscovers and critiques this classical model – a model with which Petrarch engages with a novel awareness of its limits and its brilliance and through a dialogue, at once cultural and sentimentally loaded, with a past that is rich in reflections of universal significance, in the spirit of emulation, and autobiographical references. L’articolo analizza le epistole 24, 3 e 4 delle Familiari di Petrarca indirizzate idealmente a Cicerone e contenenti due ritratti contrastanti dell’oratore latino dopo la scoperta di gran parte del suo epistolario. L’evolversi di giudizi, morali e letterari, espressi da Petrarca è oggetto di indagine con attenzione al suo acuto spirito moderno nella critica e riscoperta del modello classico con nuova consapevolezza dei suoi limiti e della sua eccellenza, in un dialogo culturale e sentimentale con il passato ricco di riflessioni di validità universale, spirito di emulazione, riferimenti autobiografici. L’article analyse les épîtres 24, 3 et 4 des Familiares de Pétrarque, idéalement adressées à Cicéron et contenant deux portraits contrastés de l’orateur latin après la découverte d’une grande partie de sa correspondance. L’évolution des jugements, moraux et littéraires, exprimés par Pétrarque, fait l’objet d’une enquête attentive à son esprit moderne et aigu dans la critique et la redécouverte du modèle classique avec une nouvelle prise de conscience de ses limites et de son excellence, dans un dialogue culturel et sentimental avec le passé riche en réflexions de valeur universelle, esprit d’émulation, références autobiographiques.